Weak Point Teacher Education: Empirical Results on Geography Teachers' Understanding of Discipline and Teaching Methods in Thuringia - Kanwischer, Detlef (Journal of Geography Education, 2008)
The first OECD PISA-study has shown alarming results in relation to German school education system. These results have attracted a number of critical statements from different institutions regarding the education of school teachers. This also included critical examinations of institutions responsible for teacher trainings. The aim of this text is to show, how the reform targets established within the post-PISA debate can be implemented into the German school teacher training system. It presents empirical primary data based on a survey conducted on Geography teachers in Thuringia. The main focus of this survey was placed on teacher's own thinking on discipline and teaching methods. A key finding of the survey has been that although it remains difficult to change the ways of thinking and teaching Geography in short-to-mid-term periods, a general transition of the teaching content and methods can be achieved. This demands a teacher's training based on positive educational experiences with new thinking and methods. In addition, these positive educational experiences can be enhanced by taking the teacher's individual professional biography into account.